PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN PROSES PEMBELAJARAN SISWA SEKOLAH DASAR JUNTINYUAT INDRAMAYU - Ahmad Fauzan; Akhmad Rifa; Vina Shelfiana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses how the application of the Make a Match learning model in improving the students’ learning processes and activities in natural sciences learning for the fourth grade of the elementary school Juntinyuat in Indramayu. The research method used was a Classroom Action Research (CAR) by applying the Kemmis and Mc Taggart model, which was conducted in two cycles. Data collection techniques include observation, documentation, and tests. The research subjects involved 21 students of Class IV. The data analysis technique applied was Milles & Huberman’s technique, which included data collection, data display, data reduction, and drawing conclusions. The results showed that the Make a Match learning method was able to improve the students’ learning process for the fourth grade of the elementary school in Juntinyuat in natural sciences learning. It could be seen from the average value of post-test in cycle 2 was 70.95, which was greater than the average value of post-test cycle 1 was 60.47 and the average value of pretest was 53.57 with the value of 70 as the KKM value. In addition, the percentage of learning completeness in cycle 2 was 85.70% higher than in cycle 1 52.80% and pretest was 23.80% and KKM was 70%. Based on the research results, the Make a Match learning model could be tried and applied by teachers in the learning process in their classrooms, either both for science lessons or other lessons, either both in grade IV of elementary school or in other classes, and either both in elementary school or in junior high school. In addition, the researcher invites further research and recommends other teachers to be motivated to conduct research and improvements to improve the learning process in the classroom by applying various models and learning media that are good, creative, innovative, and fun for students